Parenting stress and associated factors in healthcare workers after the second wave of COVID-19 in India: a two-center cross-sectional study - Kalrao, Vijay; Srivastava, Leena; Kumar, Shruti (Frontiers in Psychiatry, 2023)
Background High parenting stress (PS) in members of the general population during the COVID-19 pandemic was exacerbated by work-, family-, and child-related factors. However, the negative effects of PS on the mental health and work participation of healthcare workers (HCWs) have received limited attention. This study aimed to examine the proportion of severe PS among HCWs and identify its contributory factors. Methods This cross-sectional survey was conducted in two COVID-19-care hospitals attached to medical colleges in India between November 1 and December 24, 2021, following the delta variant-driven second wave of COVID-19. The study recruited 662 HCW parent and child dyads (aged 1.5–18 years) and assessed workplace, family, and child-related characteristics. The Parenting Stress Scale (PSS) and Child Behavior Checklist (CBCL) were used to identify severe PS and child behavioral issues, respectively. Univariable and multivariable logistic regression analyzes were used to identify the significant and independent risk factors associated with severe PS, respectively. Results Equal proportions of medical and paramedical HCWs completed the survey [mean age: 36.96 ± 5.89; female: 466 (70%)]. The median PSS score of HCWs was 33 [interquartile range (IQR): 28–39], and 23% (155/662) of the HCW parents experienced severe PS. The independent predictors of severe PS included the female sex [adjusted odds ratio (aOR): 3.31; 95% confidence interval (CI): 1.74–6.29], HCWs with >15-day postings in COVID-19 care (aOR: 3.74; 95% CI: 1.53–9.16), having children with behavioral issues (aOR: 3.49; 95% CI: 1.29–9.48), HCWs at the Dehradun center (aOR: 2.25; 95% CI: 1.24–4.10), having an HCW spouse simultaneously working in COVID-19 care (aOR: 1.88; 95% CI: 1.01–3.49), and HCWs with joint families (aOR: 1.93; 95% CI: 1.17–3.18). Conclusion Overall, 23% of the cohort of HCWs continued to experience severe PS after the second COVID-19 wave driven by the delta variant in India. Routine screening of HCWs for PS using the PSS or similar measures, anticipatory guidance for parenting, and targeting at-risk HCWs with appropriate supportive measures may help reduce the incidence of severe PS and optimize the participation of HCWs in the fight against current and future pandemic-like situations.